Probing Excimers of Pt(II) Compounds with Phenyl‐1, 2, 3‐Triazolyl and Pyridyl‐1, 2, 4‐Triazolyl Chelate Ligands by Means of Electrochemiluminescence. Issue 7 (24th February 2017) - Xiang, Guiming; Wang, Xiang; Li, Michelle S. M.; Lac, Kevin; Wang, Suning; Ding, Zhifeng
Abstract: Pt(II) complexes are well known for their excellent phosphorescence properties. Here, we report the results of an electrochemical and electrochemiluminescence (or electrogenerated chemiluminescence, ECL) study of two Pt complexes with phenyl‐1, 2, 3‐triazolyl and pyridyl‐1, 2, 4‐triazolyl chelate ligands to explore their effectiveness as ECL luminophores. The two Pt complexes with the two substituents CF3 and t‐Bu on the pyridyl‐1, 2, 4‐triazolyl ligand (Pt1 and Pt2) were purposely chosen to see the structure and ECL correlations. It was discovered that excimers, the excited states of analyte dimers, contributed mainly to the ECL production. These two complexes exhibited weak ECL efficiencies following the annihilation mechanism. However, ECL was enhanced with co‐reactants such as tri‐ n ‐propylamine for Pt1 and ammonium persulfate for Pt2. Spooling ECL spectroscopy was utilized to gain analytical insight into light emission mechanisms. It is shown that excimers were probed easily by means of ECL. Abstract : Light the way : Electrochemiluminescence (ECL) of two Pt(II) complexes with phenyl‐1, 2, 3‐triazolyl and pyridyl‐1, 2, 4‐triazolyl chelate ligands is reported. It is shown that excimers, the excited states of analyte dimers, contribute mainly to the ECL production in both annihilation and co‐reactant paths (see picture).